Performance of ultrasound as a second line test to serum CA125 in ovarian cancer screening1. (December 2014) - Menon, Usha; Talaat, Ahmed; Rosenthal, Adam N.; Macdonald, Nicola D.; Jeyerajah, Arjun R.; Skates, Steven J.; Sibley, Karen; Oram, David H.; Jacobs, Ian J.
Abstract: Objective: To assess the performance of ultrasonography in a multimodal ovarian cancer screening strategy. Design: Prospective ovarian cancer screening trial between December 1986 and June 1993. Setting: General practice, occupational health departments and an ovarian cancer screening clinic at a London teaching hospital. Population: Postmenopausal women, ≥ 45 years with a raised CA125. Methods: Volunteers with a CA125 ≥ 30 U/mL underwent a pelvic ultrasound. Scans were classified as normal, abnormal (ovarian volume ≥ 8·8 mL) or equivocal (normal volume with abnormal morphology). Abnormal ovarian morphology was subclassified as simple cyst (single, thin walled cyst with no septa or papillary projections) or complex (all other abnormalities). Volunteers with abnormal scans were referred for a gynaecological opinion. Follow up was via the cancer registry and postal questionnaires. Main outcome measures: Sensitivity, specificity and positive predictive value of different ultrasound criteria for detection of index cancer (e.g. primary invasive epithelial carcinoma of the ovary and fallopian tube). Results: Seven hundred and forty‐one women underwent 1219 scans and 20 index cancers occurred during a median follow up of 6·8 years. The sensitivity for detection of ovarian cancer of different ultrasound criteria was 100% for abnormal morphology, 89·5% for abnormal volume and 84% for complex morphology. The highest specificity (97%) and positive predictive value (37·2%) was achieved using complex morphology. Conclusion: A variety of ultrasound criteria can achieve high sensitivity, specificity and positive predictive value for index cancers in postmenopausal women with an elevated CA125. Use of ovarian morphology to interpret ultrasound may increase sensitivity and use of complex ovarian morphology may increase the positive predictive value.